Journal Management Training - Ach. Baidowi; Chasan Ma’ruf; Abdul Hamid Bashori (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2025)
Journal management training in higher education institutions is essential to enhance publication quality through a comprehensive understanding of peer review, ethics, technology, bibliometrics, management strategies, and case studies of successful journal practices. This training aims to build the capacity of journal managers at the Institut Agama Islam Pemalang to proficiently utilize Open Journal Systems (OJS) effectively, expedite the editorial process, and improve the overall quality of scientific journal management. The Journal Management Training was conducted on May 16–17, 2025, employing a Participatory Action Research approach with 12 participants divided into two classes, focusing on reviewers and OJS management, utilizing laptops and projectors. Reflective observations from practical sessions indicate that the journal managers at Institut Agama Islam Pemalang have developed a sound understanding of operating the Open Journal Systems platform. They demonstrated the ability to effectively perform various functions within the system, ranging from manuscript management to editorial processes. Moreover, the reviewers showed adequate comprehension in providing comments and feedback according to the journal template sequence established in OJS. In conclusion, the training successfully enhanced the human resource capacity in journal management, which is expected to support the smooth operation and quality of scientific journal publication.